Financial Feasibility Study and Development Strategy of Uwi Farming as Local Food in Wangi-Wangi District - Febrihidayati; Marsuki Iswandi; La Ode Kasno Arif (International Journal of Technology and Education Research, 2025)
This study aims to find out the level of financial feasibility and how the development strategy of uwi farming as a local food in Wangi-Wangi District. The determination of the research location was determined deliberately with a sample of 46 respondents for financial feasibility and 5 expert respondents for the needs of Uwi's farming development strategy. The collection of research data was carried out from June to July 2024 in Waginopo, Sombu and Patuno Villages. The analysis in this study uses the R/C ratio to determine financial feasibility and the Analytical Hierarchy Process (AHP) method to determine the farming development strategy. The results of the study show that uwi farming as a local food in Wangi-Wangi District is feasible to be developed where the average total production cost is Rp 1,579,614 per season, the total revenue is Rp 4,741,304 per season and the R/C ratio is 3.0. The results of the analysis using the AHP method show that the right development strategy for uwi farming is obtained criteria and strategies are the Strengthening Food Security criteria (0.501) and alternative strategies, namely Diversified Processed Food (0.268).